Childhood cancer confers increased risk of migraine – A Danish nationwide register study. (December 2022) - Davidsson, Olafur B.; Rostgaard, Klaus; Hjalgrim, Lisa Lyngsie; Chalmer, Mona A.; Olofsson, Isa A.; Søegaard, Signe Holst; Winther, Jeanette F.; Kenborg, Line; Hansen, Thomas F.; Hjalgrim, Henrik
Abstract: Background: Investigations of migraine among childhood cancer survivors have predominantly relied on self-reported information and hospital discharge diagnoses. Alone, both approaches are liable to bias. We used Danish nationwide registers to obtain data on both prescriptions of acute migraine medications (antimigraines) and hospital discharge diagnoses of migraine to assess the relative risk of migraine across a wider spectrum of migraine presentations than previously studied. Methods: We followed a Danish population-based cohort of 7771 individuals with childhood cancer diagnosed in the period from Jan 1st, 1978 to Dec 31st, 2017, for risk of prescription antimigraine initiation and for risk of hospitalization due to migraine. Rates of hospitalization were assessed for the entire follow-up period whereas rates of antimigraine initiations were assessed in the period from Jan 1st, 1997, to Dec 31st, 2017. Relative to the general population without childhood cancer, standardized incidence ratios (SIRs) were calculated for each outcome. Results: Individuals exposed to childhood cancer were at increased risk of antimigraine initiation (SIR of 1.24, 95% CI: 1.11–1.38) and of migraine hospitalization (SIR of 2.44, 95% CI: 1.87–3.12) from the day of their cancer diagnosis and up to 40 years after. Conclusions: Individuals diagnosed with childhood cancer have a higher risk of migraine of varying presentations, in addition to migraine resulting in hospitalization as previously reported. This potentially preventable problem warrants clinical attention. Highlights: Danish nationwide registers give unbiased estimates of migraine prevalence among individuals diagnosed with childhood cancer. Childhood cancer confers increased risk of initiating prescription migraine therapy and being hospitalized for migraine. Individuals diagnosed at 15-19 years of age reflect an increased burden of psychological sequela compared to younger peers.